Market Orientation and Hotel Industry: Developing a Measurement Model - Sampaio, Carlos Alberto Fernandes (2018)
This study seeks to fill a gap in market orientation literature about the hotel industry and deals with the construction of a market orientation scale tailored based on a sample obtained from the hotel industry in a multicultural context. The proposed model has three dimensions: intelligence generation, intelligence dissemination and coordinated response to the client, competition and market structure domains. Research results indicate that the scale has good psychometric indicators. Content validity was assessed by questioning a group of marketing experts across Western Europe. Working data indicates that the proposed model holds convergent and discriminant validity as well reliability.